Are the Verbal TTCT Forms Actually Interchangeable?. (4th August 2022) - Grajzel, Katalin; Dumas, Denis; Acar, Selcuk
ABSTRACT: One of the best‐known and most frequently used measures of creative idea generation is the Torrance Test of Creative Thinking (TTCT). The TTCT Verbal, assessing verbal ideation, contains two forms created to be used interchangeably by researchers and practitioners. However, the parallel forms reliability of the two versions of the TTCT Verbal has not been examined for over 50 years. This study provides a long‐needed evaluation of the parallel forms reliability of the TTCT Verbal by correlating publisher generated and text‐mining‐based scores across the forms. The relatively weak relationship between the two forms, ranging between .21 and .40 for the overall TTCT Verbal and ranging between .03 and .33 for the individual TTCT Verbal tasks, suggests that caution should be exercised when researchers and practitioners use the two forms as equivalent measures of verbal creative idea generation.